Innvandrerkvinners erfaringer med svangerskap, fødsel og barseltid i Norge - en kvalitativ studie - Egge, Hilde; Kvellestad, Kristine; Glavin, Kari (Nordisk tidsskrift for helseforskning, 2018)
Right to equal healthcare is statutory in Norway, but there is little knowledge of immigrant women’s experiences of health- and welfare services during pregnancy and the portnatal period. Immigrant women are at higher risk for a number of complications related to this period. The purpose of this study was to acquire deeper insight into immigrant women’s needs and experiences during their pregnancy, childbirth and the postnatal period in Norway. The study has a qualitative design using in-depth interviews of immigrant women during pregnancy and the postnatal period. The results are divided into four categories; networks, health professionals have different approaches, the father`s role, and knowledge and information. Results show that language is an important prerequisite for equitable and culture-sensitive health services. Mutual understanding has to be established for the woman’s needs to be met and to experience co-determination and recognition. More attention to the father’s role is suggested. equal healthcare; immigrant women; qualitative design; birth; postnatal period likeverdige helsetjenester; innvandrerkvinner; kvalitativt design; fødsel; barseltid